Biological pretreatment of rice straw with cellulase-free xylanolytic enzyme-producing Bacillus firmus K-1: Structural modification and biomass digestibility. (November 2020) - Baramee, Sirilak; Siriatcharanon, Ake-kavitch; Ketbot, Prattana; Teeravivattanakit, Thitiporn; Waeonukul, Rattiya; Pason, Patthra; Tachaapaikoon, Chakrit; Ratanakhanokchai, Khanok; Phitsuwan, Paripok
Abstract: Biological pretreatment using microorganisms or enzymes offers an eco-friendly process for biomass processing. Herein, the efficiency of pretreatment of rice straw with the cellulase-free xylanolytic enzyme-producing Bacillus firmus K-1 and its enzymes was assessed. After pretreatment with strain K-1 (BRS), the xylan content in rice straw reduced significantly (21% removal), thus increasing exposure of the cellulose crystal structure (Crystallinity index (CrI) = 40.2%) and creating biomass porosity. Subsequent treatment of BRS with the in-house xylanase preparation (BRS-E) slightly increased xylan removal (30% removal). The reduction of xylan thus led to larger pore size and increased crystallinity (CrI = 42.8%). Compared to untreated rice straw (24% glucan conversion), hydrolysis of BRS and BRS-E with the commercial cellulase preparation Accellerase 1500 at 100 g/L substrate load showed comparable glucose yield, giving about 74% glucan conversion. The results indicate that the removal of xylan can enhance accessibility of cellulose to cellulases, although the lignin content was not reduced (24% for BRS and 25% for BRS-E). This work demonstrates a new insight into the improvement of pretreatment efficiency using a xylan-degrading microorganism, which is an alternative to conventional lignin removal by fungal pretreatment. Highlights: Pretreatment of rice straw (RS) with xylanolytic Bacillus firmus K-1 was proposed. RS pretreated with strain K-1 (BRS) had low xylan and high cellulose content. Pretreatment of BRS with xylanases (BRS-E) removed more xylan and created porosity. BRS and BRS-E increased free cellulose surfaces with little effect on lignin. BRS and BRS-E gave comparable glucan conversion yield (∼74%).